2017
DOI: 10.1371/journal.pone.0173107
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative pain treatment after total knee arthroplasty: A systematic review

Abstract: IntroductionThe aim of this systematic review was to document efficacy, safety and quality of evidence of analgesic interventions after total knee arthroplasty (TKA).MethodsThis PRISMA-compliant and PROSPERO-registered review includes all-language randomized controlled trials of medication-based analgesic interventions after TKA. Bias was evaluated according to Cochrane methodology. Outcomes were opioid consumption (primary), pain scores at rest and during mobilization, adverse events, and length of stay. Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
101
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(117 citation statements)
references
References 114 publications
2
101
0
6
Order By: Relevance
“…Changes in the degree of pain can be assessed by VAS. Karlsen et al conducted a meta-analysis of pain management after TKA and found that there is no best strategy for pain management after TKA, in the literature (22). In our study, the improvement of patients' postoperative pain in this study is similar to that of Wang et.…”
Section: Discussionsupporting
confidence: 85%
“…Changes in the degree of pain can be assessed by VAS. Karlsen et al conducted a meta-analysis of pain management after TKA and found that there is no best strategy for pain management after TKA, in the literature (22). In our study, the improvement of patients' postoperative pain in this study is similar to that of Wang et.…”
Section: Discussionsupporting
confidence: 85%
“…Typical doses of bupivacaine are in the range of 30–300 mg when delivered by intra‐articular injection or local infiltration . Our results showed that during the first three days the effective daily dose of bupivacaine being eluted from a bupivacaine‐loaded UHMWPE can be in this range.…”
Section: Discussionmentioning
confidence: 63%
“…Typical doses of bupivacaine are in the range of 30-300 mg when delivered by intra-articular injection or local infiltration. 25,41 Our results showed that during the first three days the effective daily dose of bupivacaine being eluted from a bupivacaine-loaded UHMWPE can be in this range. Although it is difficult to correlate in-vitro and in-vivo drug release kinetics, our results showed that it is possible to deliver clinically-relevant doses of bupivacaine for pain management from bupivacaine-loaded UHMWPE implants for at least 3 days.…”
Section: Discussionmentioning
confidence: 70%
“…Variability in measurement times across the seven studies examining pain outcomes led to the conclusion that patients undergoing hip or knee surgery experience postoperative pain at several time points during their hospitalization. Given the seven included studies on pain outcomes combined their music intervention with standard care, this difference in findings could be the result of heterogeneity of trial designs and lack of an optimal procedure‐specific analgesic regimen after hip or knee surgery (Karlsen et al., ). It is, therefore, reasonable to suggest that there is no consensus on when pain is mostly experienced, following hip or knee surgery, thus making it difficult to suggest a specific time point when music should be administered.…”
Section: Discussionmentioning
confidence: 99%